Boosting enzymatic degradation of cellulose using a fungal expansin: Structural insight into the pretreatment mechanism. (August 2022) - Ding, Sunjia; Liu, Xiaoqing; Hakulinen, Nina; Taherzadeh, Mohammad J.; Wang, Yaru; Wang, Yuan; Qin, Xing; Wang, Xiaolu; Yao, Bin; Luo, Huiying; Tu, Tao
Graphical abstract: Highlights: Tl EXLX1, a fungal expansin, promotes cell wall extension and cellulose degradation. Tl EXLX1 exhibits varying degrees of synergistic action with commercial cellulase. Y291, W292, and Y327 CH–π interactions with glucose units mediate cellulose binding. T179, D237, and D248 mediate cellulose loosening by disrupting H-bonding network. Tl EXLX1 may represent a sustainable tool for the efficient utilization of cellulose. Abstract: The recalcitrance of cellulosic biomass greatly hinders its enzymatic degradation. Expansins induce cell wall loosening and promote efficient cellulose utilization; however, the molecular mechanism underlying their action is not well understood. In this study, Tl EXLX1, a fungal expansin from Talaromyces leycettanus JCM12802, was characterized in terms of phylogeny, synergy, structure, and mechanism of action. Tl EXLX1 displayed varying degrees of synergism with commercial cellulase in the pretreatment of corn straw and filter paper. Tl EXLX1 binds to cellulose via domain 2, mediated by CH–π interactions with residues Tyr291, Trp292, and Tyr327. Residues Asp237, Glu238, and Asp248 in domain 1 form hydrogen bonds with glucose units and break the inherent hydrogen bonding within the cellulose matrix. This study identified the expansin amino acid residues crucial for cellulose binding, and elucidated the structure and function of expansins in cell wall networks; this has potential applications in biomass utilization.